(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2004)
A four and half year old female child was examined by medical board with allegation of rape and sodomy under general anesthesia. On examination, there was no evidence of injury to genitalia and anal region. Vaginal and anal swabs were taken; smears were prepared and sent for analysis to FSL. The hymen was intact. However five bruises were present on different parts of the body 2 to 4 days duration. She was not wearing the same undergarment, hence was not preserved.